Association between estimated glucose disposal rate and metabolic dysfunction-associated steatotic liver disease and dyslipidemia in US adults: a cross-sectional study - Liu, Deliang; Lv, Xiaojun; Li, Wenwen; Dai, Hongsheng; Tan, Yang; Yang, Dandan; Zhang, Xiaoqian (Frontiers in Nutrition, 2025)
BackgroundMetabolic dysfunction-associated steatotic liver disease (MASLD) is strongly associated with insulin resistance (IR). This study examined the relationship between estimated glucose disposal rate (eGDR), a simple IR indicator, and MASLD risk.MethodsUsing NHANES 2017–2018 data (n = 3,957), MASLD was diagnosed by CAP ≥285 dB/m. eGDR was calculated from waist circumference, hypertension, and HbA1c.ResultsLower eGDR significantly predicted higher MASLD risk (OR = 0.396, p < 0.01) and elevated CAp values (b = −21.375, p < 0.01). It also correlated with unfavorable lipid profiles (lower HDL, higher triglycerides). Subgroup analyses showed consistent associations across age, sex, and diabetes status.ConclusionEstimated glucose disposal rate was significantly associated with both MASLD and dyslipidemia. eGDR may serve as a useful indicator for identifying risk factors related to these metabolic disorders. Mediation analysis revealed that relative fat mass (RFM), (high-density lipoprotein cholesterol) HDL, triglyceride (TG), visceral adiposity index (VAI), and uric acid to HDL ratio (UHR) mediated the association between eGDR and MASLD, with respective proportions of 61.09, 6.79, 6.53, 9.85, and 12.9%.